2011
DOI: 10.1371/journal.pone.0024842
|View full text |Cite
|
Sign up to set email alerts
|

Role of C/EBPβ Transcription Factor in Adult Hippocampal Neurogenesis

Abstract: BackgroundThe dentate gyrus of the hippocampus is one of the regions in which neurogenesis takes place in the adult brain. We have previously demonstrated that CCAAT/enhancer binding protein β (C/EBPβ) is expressed in the granular layer of the dentate gyrus of the adult mouse hippocampus. Taking into account the important role of C/EBPβ in the consolidation of long term memory, the fact that newborn neurons in the hippocampus contribute to learning and memory processes, and the role of this transcription facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 36 publications
4
41
0
Order By: Relevance
“…This suggests a role for C/EBPβ promoting neurogenesis which is supported by the upregulation of C/EBPβ in neuronal A c c e p t e d M a n u s c r i p t 47 differentiation in human neural stem cells in vitro (Cheeran et al 2005) and in murine neural progenitor cells in the subventricular zone in vivo ). In agreement with this, C/EBPβ deficient mice show reduced neurogenesis in vitro and in vivo (Cortes-Canteli et al 2011). Therefore, with the exception of one study reporting that C/EBPβ inhibition is associated with TNFα-induced neuronal differentiation of neural stem cells (Zhang et al 2012a), most experimental data support a role for C/EBPβ in promoting neurogenesis.…”
Section: Neurogenesismentioning
confidence: 60%
“…This suggests a role for C/EBPβ promoting neurogenesis which is supported by the upregulation of C/EBPβ in neuronal A c c e p t e d M a n u s c r i p t 47 differentiation in human neural stem cells in vitro (Cheeran et al 2005) and in murine neural progenitor cells in the subventricular zone in vivo ). In agreement with this, C/EBPβ deficient mice show reduced neurogenesis in vitro and in vivo (Cortes-Canteli et al 2011). Therefore, with the exception of one study reporting that C/EBPβ inhibition is associated with TNFα-induced neuronal differentiation of neural stem cells (Zhang et al 2012a), most experimental data support a role for C/EBPβ in promoting neurogenesis.…”
Section: Neurogenesismentioning
confidence: 60%
“…The C/EBP family is comprised of basic leucine zipper transcription factors that participate in multiple process of tissue homeostasis through regulation of cell proliferation and differentiation5354. C/EBPβ is thought to be particularly important for neural stem cell maintenance and neural regeneration565758. Cortes-Cantei et al ., showed that C/EBPβ plays a critical role in neurogenesis in the adult hippocampus, where it is expressed in the newly generated neural stem cells of the dentate gyrus (DG).…”
Section: Discussionmentioning
confidence: 99%
“…Cortes-Cantei et al ., showed that C/EBPβ plays a critical role in neurogenesis in the adult hippocampus, where it is expressed in the newly generated neural stem cells of the dentate gyrus (DG). Loss of C/EBPβ results in reduced cell proliferation and impaired differentiation of newly generated neurons in the adult hippocampal DG in vivo 57. Zhang et al .…”
Section: Discussionmentioning
confidence: 99%
“…43 By performing a double luciferase assay, the transcription factor 43 By performing a double luciferase assay, the transcription factor …”
Section: Rik-201 and Rik-203 May Be Regulated By C/ebpβ And Associamentioning
confidence: 99%
“…Sox6 restored the mESC neural differentiation to NPCs repressed by knockdown of the Rik-201 and Rik-203. Mice lacking C/EBPβ present reduced survival of newborn cells in the hippocampus, a decrease in the number of these cells that differentiate into neurons, and a diminished number of cells that proliferate in the subgranular zone of the dentate gyrus 43. However, there are currently no studies that show the potential impact of miRNA/Sox6 regulatory pathway on the neural development-related process.…”
mentioning
confidence: 99%